1993
DOI: 10.1254/jjp.63.159
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Airway Hyperreactivity by (±)Salbutamol in Sensitized Guinea Pigs

Abstract: ABSTRACT-In guinea pigs passively sensitized to ovalbumin, sustained (6 days) subcutaneous infusion of (±)salbutamol (1 mg/kg/day) induced significant airway obstruction and heightened responsivity to airway spasmogens. Of these animals, a substantial proportion (78/235) were too responsive to injected spasmogens to permit infusion of ovalbumin or died following infusion of ovalbumin; yet there were few deaths (2/166) amongst the sensitized animals not exposed to (±)salbutamol.In comparison to the animals not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 19 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…Although, Ssalbutamol induced a weak relaxation of equine isolated bronchi pre-contracted by histamine, it induced an increase in airway smooth muscle responsiveness to the cumulative dose response to this spasmogen in both normal and RAO bronchi. In agreement with these findings, racemic salbutamol induced an exaggerated conctractile response to histamine in airway tissues obtained from sensitized from guinea pigs [21]. It has been speculated that the pro-inflammatory and pro-constrictory activity of S-isomer, are mediated by the activation of transcriptional nuclear factor κB (NF-κB) as has been demonstrated in human isolated airways [23],.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although, Ssalbutamol induced a weak relaxation of equine isolated bronchi pre-contracted by histamine, it induced an increase in airway smooth muscle responsiveness to the cumulative dose response to this spasmogen in both normal and RAO bronchi. In agreement with these findings, racemic salbutamol induced an exaggerated conctractile response to histamine in airway tissues obtained from sensitized from guinea pigs [21]. It has been speculated that the pro-inflammatory and pro-constrictory activity of S-isomer, are mediated by the activation of transcriptional nuclear factor κB (NF-κB) as has been demonstrated in human isolated airways [23],.…”
Section: Discussionsupporting
confidence: 66%
“…In line with these results, it has been documented that detrimental effects of the racemic mixture of β 2 -agonists are strictly related to the S-isomers [2,6,21,22]. Although, Ssalbutamol induced a weak relaxation of equine isolated bronchi pre-contracted by histamine, it induced an increase in airway smooth muscle responsiveness to the cumulative dose response to this spasmogen in both normal and RAO bronchi.…”
Section: Discussionmentioning
confidence: 54%
“…(S) -Albuterol was originally thought to be pharmacologically inert, but has since been found to induce exaggerated airway reactivity and exacerbate asthmatic conditions [7, 8]. (S) -Albuterol increases intracellular calcium and airway hyperresponsiveness to spasmogens [9, 10]. (S) -Albuterol is metabolized more slowly than levalbuterol [11, 12], so that, depending on the frequency and intervals of repeated dosing, the levels of (S) -albuterol in tissues in vivo may exceed those of levalbuterol, and thereby may contribute to the cumulative adverse effects of (S) -albuterol.…”
Section: Introductionmentioning
confidence: 99%
“…The dose was therefore doubled which resulted in detectable plasma concentrations. Blood samples were collected before and at 5,8,11,15,30,45,60,90,120,180 and 240 min after the salbutamol aerosol was instilled. Urine was not collected in this set of experiments.…”
Section: Subjectsmentioning
confidence: 99%
“…Racemic R,S-salbutamol is taken for the relief of reversible bronchoconstriction and the therapeutic activity is associated with the R-enantiomer [2±4]. S-salbutamol has been demonstrated to cause increased airway responsiveness to carbachol in vitro and in vivo (in guinea-pigs) [5,6]. Previously it has been shown that metabolism occurs in both airways and the gastrointestinal tract by stereoselective sulphate conjugation [7].…”
mentioning
confidence: 99%